Sustainable energy transition towards decarbonization among developing countries: a systematic literature review - Joshi, Sudhanshu; Sharma, Manu; Kumar, Anil; Joshi, Tanuja; Johri, Amar; Alfehaid, Muhannad (Frontiers in Sustainability, 2025)
IntroductionSustainable energy transitions have become an urgent global necessity. However, developing countries face critical challenges at the intersection of rising energy demand, inadequate infrastructure, constrained financial resources, and increasing climate commitments. Understanding how these nations navigate the shift toward sustainable energy systems is essential to accelerating global decarbonization.MethodsThis systematic review employs the DASOBI framework to synthesize empirical evidence on energy mix transitions and decarbonization pathways in developing countries between 2010 and 2025. Research questions were developed using the PICOS model, and 17 peer-reviewed studies were identified and analyzed in accordance with PRISMA guidelines to ensure methodological rigor.ResultsFindings reveal divergent transition trajectories among developing countries. Nations such as Morocco and Brazil demonstrate progress through effective institutions, supportive policy environments, and access to concessional financing, achieving measurable decarbonization outcomes. In contrast, countries like Nigeria and South Africa continue to encounter persistent barriers, including fossil fuel lock-in, limited governance capacity, and institutional inertia. Despite increasing technological acceptance, regulatory weaknesses, deficient sub-national capabilities, and societal resistance hinder broader systemic change.DiscussionThis review highlights that sustainable energy transition in developing contexts remains constrained by structural and institutional barriers. Nonetheless, adaptive, inclusive, and impact-focused policy frameworks can foster long-term transformation. The findings underscore the necessity of strengthening governance, improving access to finance, and promoting collaborative frameworks to accelerate decarbonization in the Global South.